The Synthesis of Anatase Nanoparticles and the Preparation of Photocatalytically Active Coatings Based on Wet Chemical Methods for Self-Cleaning Applications - Dejan Verhovšek; Nika Veronovski; Urška Lavrencic Štangar; Marko Kete; Kristina Žagar; Miran Ceh (International Journal of Photoenergy)
We report on an improved sol-gel method for the production of highly photocatalytic titanium dioxide (TiO2) anatase nanoparticles which can provide appropriate control over the final characteristics of the nanoparticles, such as particle size, crystallinity, crystal structure, morphology, and also the degree of agglomeration. The synthesized anatase nanoparticles were characterized using various techniques, such as X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), and were tested in coatings for self-cleaning glass and ceramic surfaces. The coatings were prepared using a soft chemistry route and are completely transparent to visible light and exhibit a high photocatalytic effect, which was determined by contact-angle measurements. Finally, it is worth mentioning that both the sol-gel synthesis method and the coating-preparation method are based on a wet chemical process, thus presenting no risk of handling the TiO2 anatase nanoparticles in their potentially hazardous powder form at any stage of our development. Low-price, easy-to-handle, and nontoxic materials were used. Therefore, our work represents an important contribution to the development of TiO2 anatase nanoparticle coatings that provide a high photocatalytic effect and can thus be used for numerous applications.